Establishment of Over-The-Scope-Clips (OTSC®) in daily endoscopic routine. Issue 2 (March 2017) - Honegger, C; Valli, PV; Wiegand, N; Bauerfeind, P; Gubler, C
Background: Alongside the evolution of interventional endoscopy, the need for a more sophisticated closure tool tailored to the treatment of new challenging indications has been increasing rapidly. Methods: We here present our collected data on 262 Over-The-Scope-Clip (OTSC®) placements in a total of 233 interventions at our institution. Follow-up was focused on clinically lasting success with regards to different indications. Results: Immediate success of OTSC® treatment was observed in 87.1% of all sessions (203/233). The success rates per indication were as follows: spontaneous bleeding 84.8% (28/33); iatrogenic bleeding 100% (20/20); acute perforation 90.3% (65/72); prophylaxis for perforation 100% (24/24); anastomotic leakage 61.1% (11/18); fistulae 80.7% (46/57); diameter reduction of the gastrojejunal anastomosis 100% (6/6); and stent fixation 100% (3/3). At 30-day follow-up, the overall success rate was 67.4% (157/233). The success rates per indication were as follows: spontaneous bleeding 69.7% (23/33); iatrogenic bleeding 90% (18/20); acute perforation 86.1% (62/72); prophylaxis for perforation 100% (24/24); anastomotic leakage 33.3% (6/18); fistulae 29.8% (17/57), diameter reduction of the gastrojejunal anastomosis 83.3% (5/6); and stent fixation 66% (2/3). Conclusions: Our cohort confirms previous data on the clinical usefulness of the OTSC® in daily routine practice.